Recebimento de recomendações boca-a-boca: elementos influenciadores da predisposição à aceitação - Pereira, Maise Soares (Universidade do Vale do Rio dos Sinos, 2012)
Considered over the last decades as a sociological phenomenon, word-of-mouth (WOM) has been used as a marketing tool for information diffusion, persuasion and customer winning. One of the growing company strategies due to these activities are the word-of-mouth marketing programs, which offer a group of current customers incentives to talk positively about their products/services to others. Such initiatives raise new approaches and concerns, considering possible ethical dilemmas about WOM credibility and also changing its focus from WOM givers to those who receive it. Hence, this dissertation is presented in order to fulfill the knowledge gaps of what makes someone accept a WOM recommendation and the impact of it coming from a company organized marketing program. Aiming to identify and measure sources of influence for WOM recommendation acceptance, the present study proposes, after literature review, a relational model able to correlate and measure the impact of a group of elements on WOM acceptance willingness as well as the particular effect of it being part of a company designed marketing campaign. So as to identify new and refine theoretical elements, a qualitative inquiry of 12 in-depth interviews was held which results conveyed input to a survey applied to 350 interviewees. Data collection questionnaire presented a retrospective design – inquiring about past received recommendations – and also a hypothetical scenario presentation – implying the recommendation being part of a company designed marketing program. Main model results indicate provider’s expertise as well as its similarity with receiver most related elements to WOM message and its resultant acceptance willingness. Still, findings could show company incentive does not annul recommendation acceptance willingness, however causes its reduction, suggesting caution on its usage. More detailed findings were discussed in the study, as well as its implications to academy and business community.
Keywords: Programa de marketing boca-a-boca; Recomendação boca-a-boca; Boca-a-boca incentivado; Word-of-mouth (WOM) recommendations; Company sponsored word-of-mouth; Organized WOM programs; ACCNPQ::Ciências Sociais Aplicadas::Administração